IoT-based Automatic Fish Pond Control System - Azhra, Fariza Halidatsani; Anam, Chaerul (Institut Teknologi Sepuluh Nopember, 2020)
Aquaculture is a potential sector to be developed by the people of Indonesia considering that Indonesia's territory is dominated by the sea. Based on data released by the Directorate General of Aquaculture in 2015, the level of fish consumption projected increase up to 54.49 kg/capita/year. One important factor influencing the success of aquaculture is water quality. Some physical parameters to describe water quality include temperature, degree of acidity, dissolved oxygen and turbidity. The case of the death of thousands of fish in Cirebon due to hot temperatures reaching 36 degrees Celsius in November 2015 is one proof that monitoring and control of pond water quality has not been done properly. It will cause huge losses for fisheries. With research and development methods researcher design a tool called SENDAL IKAN. This tool has 7 sensors that can control water quality in fish ponds in real time from phone and can activate automatic responses directly and through applications on mobile phones if there is an indication that the water quality is outside normal limits. That way fish farmers will be easier to control and will not be too late to handle problems related to fish pond water quality.